Optimization of a Human Bacille Calmette-Guérin Challenge Model: A Tool to Evaluate Antimycobacterial Immunity. (8th October 2015) - Minhinnick, Alice; Harris, Stephanie; Wilkie, Morven; Peter, Jonathan; Stockdale, Lisa; Manjaly-Thomas, Zita-Rose; Vermaak, Samantha; Satti, Iman; Moss, Paul; McShane, Helen
Abstract : Background. There is an urgent need for an improved tuberculosis vaccine. The lack of a validated correlate of protection slows progress in achieving this goal. A human mycobacterial challenge model, using bacille Calmette-Guérin (BCG) as a surrogate for a Mycobacterium tuberculosis challenge, would facilitate vaccine selection for field efficacy testing. Optimization of this model is required. Methods. Healthy BCG-naive adults were assigned to receive intradermal standard-dose BCG SSI (group A), standard-dose BCG TICE (group B), high-dose BCG SSI (group C), and high-dose BCG TICE (group D). Two weeks after BCG challenge, skin biopsy of the challenge site was performed. BCG mycobacterial load was quantified by solid culture and quantitative polymerase chain reaction. Results. BCG was well tolerated, and reactogenicity was similar between groups, regardless of strain and dose. There was significantly greater recovery of BCG from the high-dose challenge groups, compared with standard-dose challenge. BCG strain did not significantly affect BCG recovery. Conclusions. BCG challenge dose affects sensitivity of this model. We have selected high-dose BCG SSI to take forward in future challenge studies. Assessment of candidate tuberculosis vaccine effectiveness with this optimized model could contribute to vaccine selection for efficacy trials. Clinical Trials Registration. NCT02088892.